Peran Guru Profesional dalam memajukan Pendidikan di Era Industri 4.0 - Petrus, Wadison; Nainggolan, Dewi Suri Agustina; Talizaro Tafonao (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Abstract: The purpose of writing this article is to see what obstacles are faced by teachers in improving educational progress in the industrial era 4.0. This research is based on the community's point of view that education is the main aspect in bringing about change for the progress of the nation. This can be seen from the appreciation of the community in encouraging their children to go to school, because through education they can be freed from the shackles of ignorance and backwardness. However, this expectation has not been achieved due to the many obstacles faced by teachers in improving their professionalism in teaching as explained in this article. This paper uses a qualitative method by examining the professional role of teachers in advancing education in the industrial era 4.0. The author collects data through the study of journal articles, books and scientific works that can be trusted to support the author's analysts in writing this article. The results obtained in this study are teachers understand the meaning of professionalism in the world of education, problems in the world of education, rights and obligations in educational change, the function of the teacher's role in supporting educational progress in the industrial era 4.0. Thus, improving education in the industrial era 4.0 is the responsibility of every teacher.Abstrak: Tujuan penulisan artikel ini adalah melihat apa saja kendala yang dihadapi oleh guru dalam meningkatkan kemajuan pendidikan di era industri 4.0. Penelitian ini didasarkan dari pandang masyarakat bahwa pendidikan merupakan aspek utama dalam membawa perubahan bagi kemajuan bangsa. Hal ini terlihat dari apresiasi masyarakat dalam mendorong anak-anaknya untuk bersekolah, karena melalui pendidikan dapat dimerdekakan dari belenggu kebodohan dan keterbelakangan. Namun harapan ini masih belum tercapai disebabkan karena banyak kendala yang hadapi oleh guru dalam meningkatkan profesionalnya dalam mengajar sebagaimana penjelasan dalam artikel ini. Tulisan ini mengunakan metode kualitatif dengan mengkaji peran profesional guru dalam memajukan pendidikan di era industri 4.0. Penulis mengumpulkan data melalui kajian artikel jurnal, buku dan karya ilmiah yang dapat dipercaya untuk mendukung analis penulis  dalam penulisan artikel ini. Hasil yang diperoleh dalam kajian ini adalah guru memahami makna profesional dalam dunia pendidikan, masalah dalam dunia pendidikan, Hak dan Kewajiban dalam perubahan pendidikan, fungsi peran guru dalam mendukung kemajuan pendidikan di era industri 4.0. Dengan demikian bahwa peningkatan pendidikan di era industri 4.0 merupakan tanggung jawab setiap guru.